The Impact of Mindfulness on Nurses’ Mental Well-being and Professional Resilience: A Literature Review - Mr. R. Velmurugan; Dr. M. Abirami (The Bioscan, 2025)
Mindfulness meditation has gained increasing attention in healthcare as a strategy to enhance nurses' mental well-being, resilience, and job satisfaction. Nurses frequently experience high levels of occupational stress, burnout, and psychological distress due to the demanding nature of their profession. This literature review examines the role of mindfulness-based interventions (MBIs) in addressing these challenges. Research highlights that mindfulness improves emotional regulation, reduces anxiety and depression, and fosters resilience, ultimately contributing to better patient care. Despite its benefits, challenges such as time constraints, institutional barriers, and skepticism hinder widespread implementation. This review underscores the need for further research to assess the long-term impact, scalability, and integration of mindfulness practices in nursing education and professional settings.